Broken prey - Sandford, John, 1944 Feb. 23- (New York : G.P. Putnam's Sons, 2005)
After a series of killings emulate the works of a trio of inmates currently being held at the Minnesota Security Hospital, Lucas Davenport starts his investigation by looking for a recently released sex offender who seems to have disappeared after cutting off his court-imposed ankle bracelet.
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Private investigators -- Minnesota -- Minneapolis -- Fiction; Minneapolis (Minn.) -- Fiction; Mystery fiction